Gastric plexiform fibromyxoma: a case report and literature review - Zheng, Li; Wang, Jin (Frontiers in Oncology, 2025)
Plexiform fibromyxoma (PF) is a rare mesenchymal tumour that primarily occurs in the stomach, with the antrum and pyloric region being the most common sites. A few cases have also been reported in the duodenum, jejunum, mediastinum, gallbladder, and other locations. Over 100 cases have been reported in the literature, with more than 30 cases reported in our country. A rare case of PF occurring in the cardia and fundus of the stomach is reported in this study. The tumour tissue showed a multinodular, plexiform growth pattern between the muscle bundles of the gastric wall, in which a myxoid matrix and thin-walled vessels were visible. The tumour cells were spindle shaped or short spindle shaped, with a mild change in morphological appearance, and mitotic figures were rare. The tumour cells showed immunohistochemical expression of vimentin and SMA, with focal expression of calponin and CD10. The Ki-67 proliferation index was approximately 5%. The plexiform fibromyxoma was characterized by benign biological behaviour, with surgical excision as the primary therapy. The patient was followed up for about 2 years after surgery without any tumour recurrence or metastasis.